Green preparation of nanoscale zero-valent iron using clove extracts as adsorbent for lead removal. (February 2019) - Budi, Setia; Yusmaniar; Afida, Increase; Anugerah, Yuliana Dewi; Mahmud, Amir
Abstract: This paper reports our studies on the synthesis of nanoscale zero-valent iron (nZVI) for lead ions (Pb(II)) adsorbent. The nZVI was prepared using clove ( Syzygium aromaticum ) extracts as an environmentally-friendly reducing agent. Fourier transform infra-red spectroscopy (FTIR) studies indicate that eugenol is the main fraction found in the extracts used in this work. Dynamic light scattering (DLS) measurements show that relatively small particles with narrow size distribution were obtained by dropping the reducing agent gradually into the iron sulphate solution. The batch experiments showed that the as-prepared nZVI exhibits very high removal efficiency of Pb(II). The optimum adsorption time was reached differently for the adsorbent with different size distribution. The highest value is 96%, which was achieved at the adsorption time of 30 minutes by using CT-nZVI.